2018
DOI: 10.1111/joie.12178
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Retailers Advertise Store Brands Differently Across Product Categories?

Abstract: We provide new evidence on retailers' pricing and advertising of store brands in the U.K. grocery markets. We analyse a simple Hotelling model in which retailers and manufacturers endogenously advertise their respective brands; we account for the impact of advertising on retailer-manufacturer bargaining and downstream competition. The model predicts that retailers advertise their store brands less when advertising is more rivalrous. We present empirical evidence consistent with this prediction. According to ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…In doing so, they stand a greater chance of expanding private label customers. In support of the aforementioned, Griffith et al (2018), in their study, found that the most advertised private label products or private label product category had more purchases than those under-advertised. Therefore, this proves the positive effects that advertising has on the consumption of private label brands.…”
Section: Advertising For Private Label Brandsmentioning
confidence: 71%
“…In doing so, they stand a greater chance of expanding private label customers. In support of the aforementioned, Griffith et al (2018), in their study, found that the most advertised private label products or private label product category had more purchases than those under-advertised. Therefore, this proves the positive effects that advertising has on the consumption of private label brands.…”
Section: Advertising For Private Label Brandsmentioning
confidence: 71%
“…They find that across the 288 major brands they consider, the impact of an increase in advertising on quantity sold is modest and suggest that large advertising expenditures represent a misallocation of resources. Griffith, Krol, and Smith (2018) use scanner data across 60 product categories to study the welfare implications of retailers' pricing and advertising strategies for their own (store) brand products, showing that the presence of store brands can increase aggregate consumer surplus -when advertising is rivalrous (it benefits a specific product rather than the entire category), advertising is typically over-provided by the market, because firms do not account for the negative externalities of their advertising on other firms. When making decisions for a store brand the retailer internalizes some of the negative externalities from rivalrous advertising, and so spends less on advertising.…”
Section: Advertisingmentioning
confidence: 99%